The Influence of Information Communication Technology (ICT) integration on teaching and learning in South African Schools - Meladi, O. Makgati Makgati; Olawumi D. Awolusi (Journal of Education and Vocational Research, 2020)
Despite recent emphasis on the quality of education for all in South Africa, the department of education still face major challenges that hinder the progress of implementing quality education, especially in the rural areas. Consequently, this study followed an action qualitative method. The overall purpose of the study was to determine the influence of ICT integration in on the quality of teaching and learning in the classroom and to further examine the benefits of using ICT to enhance personal growth, individual performance, critical thinking skills reading and writing skills. The research questions were semi-structured and open-ended. The researcher interviewed nine (9) learners and seven (7) teachers in a two session focus group, first session involved only teachers and last session had only grade 12 learners. The themes of the sessions were documented separately, however, relationship between the themes were identified. The study also performed observation in the classroom to access situations that would have been almost impossible to identify in an interview or a questionnaire. Results shown that a lot still need to be done by the government to initiate the process of integrating ICT in education or empower teachers with ICT skill and to do away with the traditional teaching method. The study however concluded on the positive influence of ICT integration on teaching and learning practices in the classroom for both teachers and learners. Consequently, the study recommends the following: government must provide training and incentives to encourage personal development in teachers and for young graduates to value teaching; policies about lost equipment must be drafted and understood by all parties; deployments of technology innovation, as well, as the imperatives of following the recommendation of UNESCO’s four stages of ICT integration